Antecedents and consequences of active procrastination and mediation effect of self-regulation strategies among pre-service teachers in colleges of education in Nigeria - Taura, Ali Abdullahi (2014)
This study examined motivational beliefs (self-efficacy, intrinsic goal orientation, extrinsic goal orientation, task value, and test anxiety), perfectionism and selfregulation as predictors of active procrastination among pre-service teachers in colleges of education in Nigeria. In addition, the study investigated the mediating role of self-regulation in the relationship between motivational beliefs, perfectionism and active procrastination. A total of 426 pre-service teachers (223 males, 203 females) participated in the study. A set of self-report questionnaire was used to measure the participants’ levels of procrastination, motivational beliefs, perfectionism and self-regulation. Structural equation modelling (SEM) using AMOS and SPSS software was employed as statistical technique for data analysis of the study. The findings of the study based on the output structural model, which overall goodness-of-fit indices indicate good model fit, revealed that motivational beliefs and perfectionism were not direct significant predictors of active procrastination, and active procrastination, in turn, was not found to be a significant predictor of academic achievement. However, mediation analysis, conducted in the active procrastination model of pre-service teachers, indicated that there was an evidence of indirect effects of the motivational beliefs variables and perfectionism on active procrastination through self-regulation strategies. Test of mediation by bootstrapping method established significant mediating role of self-regulation in the relationship between self-efficacy, extrinsic goal orientation, task value, test anxiety, perfectionism and active procrastination. In conclusion, the findings of the study underscore the importance of self-regulation in procrastination research. This is for the fact that self-regulation strategies were found to have considerable influence in the relationships between the predictor (self-efficacy, extrinsic goal orientation, task value, test anxiety, perfectionism) and the outcome (active procrastination) variables as well as the academic achievement of active procrastinators. In other words, active procrastination fails to explain academic achievement except through self-regulation strategies as mediator. This suggests that the reason active procrastinators can obtain satisfactory outcomes might be derived not from active procrastination itself but from their ability to apply self-regulation strategies. Thus, the findings lend a strong support to one of the general assumptions of the theory of self-regulated learning that self-regulatory activities serve as mediators between personal and contextual characteristics and actual achievement or performance. Theoretical and practical implications of the study, in addition to recommendation for future research, have been offered. For instance, as the findings of this study revealed, self-regulation is a key to understanding procrastination. Hence, the focus of future research should be on examining students’ ability to self-regulate and, therefore, procrastinate actively for successful learning and better performance.